2021
DOI: 10.1108/ijchm-07-2020-0789
|View full text |Cite
|
Sign up to set email alerts
|

Influences of artificial intelligence (AI) awareness on career competency and job burnout

Abstract: Purpose The prevalence of artificial intelligence (AI) has considerably affected management and society. This paper aims to explore its potential impact on hospitality industry employees, bringing enlightenment to both employees and managers. Design/methodology/approach Data were collected from a survey of 432 employees who worked in full-service hotels in China. Structural equation modeling (SEM) was used to analyze the data. Findings Results presented a positive relationship between AI awareness and job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 84 publications
3
79
0
5
Order By: Relevance
“…Developments in AI and its acceptance by service industries, have been translating the hospitality and tourism industries in many ways, impacting on areas, including consumer demand, tourist experiences and perceptions, destination management and prediction of tourists' behaviours (Wu et al, 2017;Filieri et al, 2021). Recent studies confirm this by demonstrating a significant correlation between AI services, the perceptions of quality, consumer happiness and engagement (Prentice et al, 2020;Mariani and Borghi, 2021;Kong et al, 2021). Several review experiments have been conducted in the hospitality and tourism literature and many have studied a diverse range of existing AI applications.…”
Section: Introductionmentioning
confidence: 95%
“…Developments in AI and its acceptance by service industries, have been translating the hospitality and tourism industries in many ways, impacting on areas, including consumer demand, tourist experiences and perceptions, destination management and prediction of tourists' behaviours (Wu et al, 2017;Filieri et al, 2021). Recent studies confirm this by demonstrating a significant correlation between AI services, the perceptions of quality, consumer happiness and engagement (Prentice et al, 2020;Mariani and Borghi, 2021;Kong et al, 2021). Several review experiments have been conducted in the hospitality and tourism literature and many have studied a diverse range of existing AI applications.…”
Section: Introductionmentioning
confidence: 95%
“…An employee's STARA awareness can be viewed as a work stressor that stimulates an employee's stressful psychological responses regarding job continuity in the future. STARA awareness has been found to associate with high job burnout and turnover intention in the hotel industry (Kong et al, 2021;Li et al, 2019).…”
Section: Employees' Stara Awareness and Challenge-hindrance Appraisalsmentioning
confidence: 99%
“…Although the prospects are critical, employees' reactions toward the firm's STARA adoption are not well documented and there is a lack of empirical investigations in the restaurant industry (Gonzalez et al, 2020;Law et al, 2019;Lu et al, 2020). A limited number of existing studies have explored the negative impact of STARA awareness on employee job-related outcomes, such as high job burnout (Kong et al, 2021) and high turnover intention (Li et al, 2019). An important question should be raised: "Will employees benefit from STARA adoption in the workplace?"…”
Section: Introductionmentioning
confidence: 99%
“…EI may also help workers in the hospitality industry by increasing their job satisfaction, which may in turn increase their performance. For example, EI may help hospitality workers deal with incivility from customers (Kim and Qu, 2019) or with other types of burnout (Kong et al , 2021). Regarding occupations overall, meta-analyses have confirmed that EI is positively related to employees’ job satisfaction and organizational commitment and is negatively related to turnover intentions (Miao et al , 2017a).…”
Section: Theory and Hypothesesmentioning
confidence: 99%